2018
DOI: 10.1111/joes.12295
|View full text |Cite
|
Sign up to set email alerts
|

Many Instruments and/or Regressors: A Friendly Guide

Abstract: This paper surveys the state of the art in the econometrics of regression models with many instruments or many regressors based on alternative -namely, dimension -asymptotics. We list critical results of dimension asymptotics that lead to better approximations of properties of familiar and alternative estimators and tests when the instruments and/or regressors are numerous. Then, we consider the problem of estimation and inference in the basic linear instrumental variables regression setup with many strong ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 105 publications
(237 reference statements)
0
6
0
Order By: Relevance
“…Assumption 1 is a technical condition on the projection matrix P. It requires the main diagonal elements of P to be bounded away from 1. This assumption is rather standard in the literature (e.g., Hausman et al, 2012;Bekker and Crudu, 2015) and is strictly weaker than the so-called asymptotic balanced design (see Anatolyev, 2018) imposed, for example, in Anatolyev and Gospodinov (2011) and Bun et al (2019) according to which all the diagonal elements of the projection matrix converge to the same constant. The assumption k → ∞ as n → ∞ formalizes the many instruments idea in a way that is known as Bekker asymptotics.…”
Section: Asymptotic Resultsmentioning
confidence: 99%
“…Assumption 1 is a technical condition on the projection matrix P. It requires the main diagonal elements of P to be bounded away from 1. This assumption is rather standard in the literature (e.g., Hausman et al, 2012;Bekker and Crudu, 2015) and is strictly weaker than the so-called asymptotic balanced design (see Anatolyev, 2018) imposed, for example, in Anatolyev and Gospodinov (2011) and Bun et al (2019) according to which all the diagonal elements of the projection matrix converge to the same constant. The assumption k → ∞ as n → ∞ formalizes the many instruments idea in a way that is known as Bekker asymptotics.…”
Section: Asymptotic Resultsmentioning
confidence: 99%
“…Despite these early cautionary tales, most inference procedures that allow for proportionality between the number of regressors, sample size, and potentially the number of restrictions, are of a more recent vintage. Here, we survey the ones most relevant to the current paper and refer to Anatolyev (2019) for a more extensive review of the literature. 1 In homoskedastic regression models, Anatolyev (2012) and Calhoun (2011) propose various corrections to classical tests that restore asymptotic validity in the presence of many restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that all of these tools are robust to weakness of the instruments as a group (though weakness of a lesser degree than that would jeopardize identification). We briefly describe these tools in the following sections; see Anatolyev (2019) for more technical details and the history of theoretical developments and suggestions of empirical strategies.…”
Section: Introductionmentioning
confidence: 99%